"Most of what they do, we cannot do!" How lay health workers respond to barriers to uptake and retention in HIV care among pregnant and breastfeeding mothers in Malawi. Issue 6 (18th June 2020) - Topp, Stephanie M; Carbone, Nicole B; Tseka, Jennifer; Kamtsendero, Linda; Banda, Godfrey; Herce, Michael E
Abstract : Background: In the era of Option B+ and 'treat all' policies for HIV, challenges to retention in care are well documented. In Malawi, several large community-facility linkage (CFL) models have emerged to address these challenges, training lay health workers (LHW) to support the national prevention of mother-to-child transmission (PMTCT) programme. This qualitative study sought to examine how PMTCT LHW deployed by Malawi's three most prevalent CFL models respond to known barriers to access and retention to antiretroviral therapy (ART) and PMTCT. Methods: We conducted a qualitative study, including 43 semi-structured interviews with PMTCT clients; 30 focus group discussions with Ministry of Health (MOH)-employed lay and professional providers and PMTCT LHWs; a facility CFL survey and 2–4 hours of onsite observation at each of 8 sites and in-depth interviews with 13 programme coordinators and MOH officials. Thematic analysis was used, combining inductive and deductive approaches. Results: Across all three models, PMTCT LHWs carried out a number of 'targeted' activities that respond directly to a range of known barriers to ART uptake and retention. These include: (i) fulfilling counselling and educational functions that responded to women's fears and uncertainties; (ii) enhancing women's social connectedness and participation in their own care and (iii) strengthening service function by helping clinic-based providers carry out duties more efficiently and effectively. Beyond absorbing workload or improving efficiency, however, PMTCT LHWs supported uptake and retention through foundational but often intangible work to strengthen CFL, including via efforts to strengthen facility-side responsiveness, and build community members' recognition of and trust in services. Conclusion: PMTCT LHWs in each of the CFL models examined, addressed social, cultural and health system factors influencing client access to, and engagement with, HIV care and treatment. Findings underscore the importance of person-centred design in the 'treat-all' era and the contribution LHWs can make to this, but foreground the challenges of achieving person-centredness in the context of an under-resourced health system. Further work to understand the governance and sustainability of these project-funded CFL models and LHW cadres is now urgently required.